Digitally Chirped Multilayer Quantum Dot Lasers with Dual-Wavelength Lasing Emissions - Yi-Jan Leo Sun; Pin-Hsien Hsieh; Gray Lin (Applied Sciences, 2019)
The dual-wavelength lasing emissions of digitally chirped multilayer quantum dot (QD) lasers are investigated both experimentally and theoretically. The two lasing wavelengths are both identified as ground-state (GS) emissions but originated from different stacks of QD multilayers. The lasing spectra exhibited broadening and splitting properties by injecting more current. Moreover, the wavelength-resolved light-current characteristics reveal that first GS lasing intensity upon the threshold of second GS transitions neither saturates nor droops with increasing injection current, but increases with slightly reduced slope efficiency. A theoretical model is developed for digitally chirped multilayer QD lasers. The simulation results qualitatively reproduce the experimental observations.